Pelatihan Pemasaran Online Berbasis Marketplace Bagi UMKM Dalam Merespon Perubahan Perilaku Konsumen - Lukmanul Hakim (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Internet users are increasing every year. According to the Indonesian Internet Service Providers Association in 2017, internet users in Indonesia accounted for 143.26 million people or 54.7 percent of the total population. Business people take advantage of this momentum by implementing online-based marketing. The community responded positively and began to switch to online shopping. There are many companies that have implemented online-based marketing which has the effect of reducing sales turnover of other companies that are not yet online. The purpose of community service activities is to improve the knowledge and skills of the company's human resources to be able to implement marketplace-based online marketing. The main activity consists of one day training for making marketplace accounts and online marketing assistance for one month. It is expected that with this activity, partner companies can develop marketplace-based online marketing independently. One day training model followed by one-month online mentoring can be used as a reference for similar activities.